2021
DOI: 10.21203/rs.3.rs-324432/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sub-second multi-channel magnetic control of select neural circuits in behaving flies

Abstract: Precisely timed activation of genetically targeted cells is a powerful tool for studying neural circuits and controlling cell-based therapies. Magnetic control of cell activity or “magnetogenetics” using magnetic nanoparticle heating of temperature-sensitive ion channels enables remote, non-invasive activation of neurons for deep-tissue applications and studies of freely behaving animals. However, the in vivo response time of thermal magnetogenetics is currently tens of seconds, which prevents the precise temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…We found that the MNMs successfully bridge the sciatic nerve gap and enable nerve signals to activate the distal muscle groups with latencies of less than 5 ms (Fig 4C). This response time is approximately 120-fold faster than any previously reported remote neural stimulation using magnetic materials ( 6 ). Unlike existing magnetic materials used for neural stimulation, we show high temporal control with our MNMs, demonstrated by both the short latency between pulse generator and the EMG response (4.06 +/- 0.209 ms) as well as the ability to drive neural responses at frequencies up to 10 Hz (Fig 4C, Fig S5).…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…We found that the MNMs successfully bridge the sciatic nerve gap and enable nerve signals to activate the distal muscle groups with latencies of less than 5 ms (Fig 4C). This response time is approximately 120-fold faster than any previously reported remote neural stimulation using magnetic materials ( 6 ). Unlike existing magnetic materials used for neural stimulation, we show high temporal control with our MNMs, demonstrated by both the short latency between pulse generator and the EMG response (4.06 +/- 0.209 ms) as well as the ability to drive neural responses at frequencies up to 10 Hz (Fig 4C, Fig S5).…”
mentioning
confidence: 65%
“…However, the cells and proteins in our body have very weak magnetic properties; thus, for magnetic fields to stimulate a biological response, researchers typically use high-field strengths in excess of 1 T that are generated by pulsed magnetics (1) or magnetic materials that convert a weak magnetic stimulus (typically less than 100 mT) into a form of energy that can stimulate nearby cells. Indeed, this materials-based approach offers superior selectivity because one can target a specific area for stimulation by limiting the location of the magnetic materials, or one can combine the magnetic materials with genetically modified cells to achieve cell-type specific neural stimulation (2)(3)(4)(5)(6)(7). A materials-based magnetic stimulation technique that could achieve millisecond timing would enable numerous neurotherapeutic applications and research applications that require neuromodulation to be precisely timed with sensory stimuli and behavior (8); however, existing magnetic materials have fallen well short of millisecond temporal precision.…”
mentioning
confidence: 99%
See 1 more Smart Citation